The impact of environmental support on health for children with hearing impairment in Taiwan - Chung-Ying Lin; Xavier C.C Fung (Wolters Kluwer Medknow Publications, 2018)
Introduction: Children with hearing impairment (HI) often encounter difficulties in learning due to their language problems caused by HI. Therefore, children with HI also suffer from health problems, including psychological health, social relationship, and school performance. Given that the International Classification of Function, Disability, and Health proposed environment as a key element in promoting health. This study proposed to investigate the impacts of environmental support on health and learning abilities among a nationally representative sample with HI. Methods: A total of 163 children (94 boys; 88 first graders and 75 third graders) retrieved from the Special Needs Education Longitudinal Study were used for analysis. Questionnaire items on environmental support (3 items), impairment (1 item), learning ability (4 items), and health (4 items) were constructed in a structural equation model. Specifically, environmental support was linked to impairment, learning ability, and health; impairment was linked to learning ability and health. Results: Our results indicated that environmental support had positive effects on three dimensions of health (social relationship, β = 0.38; emotional functioning, β = 0.27; and school performance, β = 0.59) and learning ability (β = 0.26); negative effects on impairment (β = −0.62). Impairment had negative impacts on two dimensions of health (physical fitness and school performance, β = −0.18 and −0.22, respectively) and learning ability (β = −0.29). Conclusions: According to our findings, health-care professionals and school teachers may consider establishing good environmental support for children with HI. Thus, children with HI may have improved health and learning abilities.